A new cryptic species of Polybiidae (Crustacea: Decapoda: Portunoidea) from the East Atlantic, with considerations on the genus Polybius - García-Raso, Enrique; d’Udekem d’Acoz, Cédric; Moukrim, Abdellatif; Schubart, Christoph D.; Cuesta, Jose A. (European Journal of Taxonomy, 2024)
The use of integrative taxonomy has confirmed the existence of a new distinct crab species, cryptic, within the group of the former genus Liocarcinus, now Polybius, closely related to P. holsatus, P. vernalis and P. marmoreus. Previous reports have considered it to be the Atlantic form of P. vernalis, or as a species “affinis” or “comparable to” P. holsatus. Diagnostic morphological characters are presented for identification and the morphological variability in these species, mainly within P. vernalis (the most related) is analysed. Furthermore, based on molecular and other previous data, a new combination (genus change) is proposed. This new species, Polybius dioscurus sp. nov., lives on infralittoral sandy bottoms, coexisting with the other species mentioned, in the temperate and subtropical zone of the North Atlantic Ocean, including the Alboran Sea (westernmost Mediterranean).